Meta-Analysis of Interleukin-2 Receptor Antagonists as the Treatment for Steroid-Refractory Acute Graft-Versus-Host Disease - Shen, Meng-Zhu; Li, Jing-Xia; Zhang, Xiao-Hui; Xu, Lan-Ping; Wang, Yu; Liu, Kai-Yan; Huang, Xiao-Jun; Hong, Shen-Da; Mo, Xiao-Dong (Frontiers in Immunology, 2021)
Acute graft-versus-host disease (aGVHD) is a major complication after allogeneic hematopoietic stem cell transplantation (HSCT). Corticosteroid is the first-line treatment for aGVHD, but its response rate is only approximately 50%. At present, no uniformly accepted second-line treatment for steroid-refractory aGVHD (SR-aGVHD) is available. Blocking interleukin-2 receptors (IL-2Rs) on donor T cells using pharmaceutical antagonists alleviates SR-aGVHD. This meta-analysis aimed to compare the efficacy and safety of four commercially available IL-2R antagonists (IL-2RAs) in SR-aGVHD treatment. A total of 31 studies met the following inclusion criteria: (1) patients of any race, any sex, and all ages; (2) those diagnosed with SR-aGVHD after HSCT; and (3) those using IL-2RA-based therapy as the second-line treatment. The overall response rate (ORR) at any time after treatment with basiliximab and daclizumab was 0.81 [95% confidence interval (CI): 0.74–0.87)] and 0.71 (95% CI: 0.56–0.82), respectively, which was better than that of inolimomab 0.54 (95% CI: 0.39–0.68) and denileukin diftitox 0.56 (95% CI: 0.35–0.76). The complete response rate (CRR) at any time after treatment with basiliximab and daclizumab was 0.55 (95% CI: 0.42–0.68) and 0.42 (95%CI: 0.29–0.56), respectively, which was better than that of inolimomab 0.30 (95% CI: 0.16–0.51) and denileukin diftitox 0.37 (95% CI: 0.24–0.52). The ORR and CRR were better after 1-month treatment with basiliximab and daclizumab than after treatment with inolimomab and denileukin diftitox. The incidence of the infection was higher after inolimomab treatment than after treatment with the other IL-2RAs. In conclusion, the efficacy and safety of different IL-2RAs varied. The response rate of basiliximab was the highest, followed by that of daclizumab. Prospective, randomized controlled trials are needed to compare the efficacy and safety of different IL-2RAs.